Meesiput crunchies / Raudhatul Jannah Binti Ridzuan ... [et al.] - Ridzuan, Raudhatul Jannah; Zulkifli, Nurul Azmina; Mohd Noor, Madihah; Abd Shattar, Noristisarah (2020)
MeeSiput Crunchies is an innovation of snacks food develop from original mee siput which is popular in Muar, Johor. This product aims to introduce free gluten snack food for people with celiac disease or a person who has an allergy towards gluten. This snack has been made of all-purpose gluten free flour that is mixed with xanthan gum, eggs, salt and warm water. Then, the dough was pressed into the noodle machine and the noodle were boiled until cooked. Next, formed the cooked noodle into small nest-shaped and sun-dried for three days. MeeSiput Crunchies is packed into bagged snacks and come together with special chili powder which can be shake and consume directly or mix it with water as a dipping sauce. The hedonic test with attributes of appearance, texture, aroma, crunchiness and overall acceptance had been conducted towards 31 panelists. Three (3) variances of MeeSiput Crunchies with different flour were served to the panelists; wheat flour (A), corn flour (B) and all-purpose free gluten flour (C). As the final result, sample C is the most acceptable with the higher score of texture, crunchiness and overall acceptance. Therefore, it has a good commercial value as it is suitable for all ages especially for people with gluten allergy.